2018
DOI: 10.1016/j.jaac.2018.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Thoughts and Behaviors Among First-Year College Students: Results From the WMH-ICS Project

Abstract: The distribution of STB in first-year students is widespread, and relatively independent of socio-demographic risk profile. Multivariate risk algorithms based on a high number of risk factors are indicated to efficiently link high-risk status with effective preventive interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
158
3
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 249 publications
(185 citation statements)
references
References 59 publications
(63 reference statements)
13
158
3
11
Order By: Relevance
“…It is important to note the possibility of response bias among those who received the web-based surveys. This may include higher levels of health risk behaviors (Bosnjak & Tuten, 2001; Kypri, Samaranayaka, Connor, Langley, & Maclennan, 2011) in nonrespondents compared to respondents, although other studies have recently shown high response rates associated with higher rates of suicidality (Mortier et al, 2018); it is difficult to discern the relative impacts of these potential biases. The use of self-reported diagnoses may limit the interpretation of prevalence, due to readiness of disclosure and willingness to seek services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note the possibility of response bias among those who received the web-based surveys. This may include higher levels of health risk behaviors (Bosnjak & Tuten, 2001; Kypri, Samaranayaka, Connor, Langley, & Maclennan, 2011) in nonrespondents compared to respondents, although other studies have recently shown high response rates associated with higher rates of suicidality (Mortier et al, 2018); it is difficult to discern the relative impacts of these potential biases. The use of self-reported diagnoses may limit the interpretation of prevalence, due to readiness of disclosure and willingness to seek services.…”
Section: Discussionmentioning
confidence: 99%
“…College students face unprecedented levels of distress that affect their mental health (MH) (Mortier et al, 2018). Depression, anxiety, and suicidality rates are rising among U.S. college students (Blanco et al, 2008; Eisenberg, Hunt, & Speer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, these response rates compare favourably to those achieved in other large-scale prospective college student surveys (39-44%) (Eisenberg, Hunt, & Speer, 2013; Paul, Tsypes, Eidlitz, Ernhout, & Whitlock, 2015). While it has been shown that the empirical relationship between response rate and nonresponse bias is weak (Groves, 2006), recent findings warn of potential overestimation of mental disorders when response rates are low (Mortier, Cuijpers, et al, 2018). In addition, convenience samples rather than nationally representative samples of incoming first-year students were included in our study, which may limit the representativeness of the data.…”
Section: Discussionmentioning
confidence: 99%
“…A recent metaanalysis reported that an average of 30.6% of the students suffered from depression (Ibrahim et al, 2013). This high prevalence is significant for both the distress it causes and its associated impairment in academic performance (Auerbach et al, 2016; Auerbach et al, 2018; Bruffaerts et al, 2018; Bruffaerts et al, 2012; Skidmore, Kaufman, & Crowell, 2016) as well as suicidal thoughts and behaviors (Mortier, Auerbach, et al, 2018; Mortier, Cuijpers, et al, 2018). However, research is needed to clarify how mental disorders may affect important functioning across key life domains.…”
Section: Introductionmentioning
confidence: 99%
“…The current report includes data from the first phase of the World Health Organization (WHO) World Mental Health International College Student (WMH‐ICS) initiative in which baseline surveys were completed by first year college students from 19 colleges across eight countries. In prior publications, we detailed the lifetime and 12‐month prevalence of mental disorders (Auerbach et al, ) and STBs (Mortier et al, ) and, more recently, highlighted role impairment associated with internalizing and externalizing mental disorders (Alonso et al, ). Building on this research, our current aim was to assess 12‐month psychiatric comorbidity by using a latent class analytic approach.…”
Section: Introductionmentioning
confidence: 99%